A network meta-analysis of maintenance therapy in chronic lymphocytic leukemia. - Cho-Hao Lee; Po-Huang Chen; Chin Lin; Chieh-Yung Wang; Ching-Liang Ho (PLoS ONE)
Background Chronic lymphocytic leukemia (CLL) is incurable through conventional chemoimmunotherapy regimens. Despite durable responses to front-line therapy and sustained remission rates in patients with CLL, a majority of patients eventually relapse in 5 years of initial treatment. The depth of the response may affect the length of response. Maintenance therapies were aimed to deep remissions and extend the period of disease quiescence. Lenalidomide, rituximab and ofatumumab had demonstrated some efficacy as a maintenance therapy compared to no intervention for CLL patients. The relative effect on disease control and safety between different maintenance therapies were unclear. Methods We performed a systematic literature review and network meta-analysis to evaluate relative effect on disease control and safety of current available maintenance therapies. We searched PubMed, Embase and Cochrane database up to March 6, 2019. Relevant reference of review article and conference abstract including European Hematology Association Annual Meeting (EHA 2018), American Society of Hematology Annual Meeting (ASH 2018) and American Society of Clinical Oncology Annual Meeting (ASCO 2018) were searched. Randomized controlled trials (RCT) involving current available maintenance therapy including "Lenalidomide", "Rituximab", "Ofatumumab", "Ibrutinib", "Idelalisib", "Venetoclax"and "Obinutuzumab"were eligible. Outcomes of interest included progression-free survival (PFS), overall survival (OS) and serious adverse events (SAE) in CLL patients received subsequent maintenance therapy. Two authors CHL and CL) independently assessed eligibility for all identified citations and extracted data from the original trial reports. The selected studies' risk of bias was assessed following the guidelines of Cochrane Collaboration Handbook. Results In total, six phase III RCTs with total 1,615 CLL patients were identified. Maintenance therapy using lenalidomide, rituximab, and ofatumumab demonstrated a statistically significant effect in prolongation of progression-free survival (HR:0.37, 95% CI: 0.27-0.50 of lenalidomide; HR:0.50, 95% CI: 0.38-0.66 of rituximab; HR:0.52, 95% CI:0.41-0.66 of ofatumumab, separately) compared with no intervention; however, for overall survival, the effect of maintenance therapy showed no significant difference versus no intervention (HR: 0.89, 95% CI: 0.70-1.14). Lenalidomide showed the best efficacy for PFS (HR: 0.37, 95% CI: 0.27-0.50, Probability of being best treatment: 96%). Conclusions Our network meta-analysis provided an integrated overview of relative efficacy and safety of different maintenance therapies in CLL. All maintenance therapies were effective in reducing the risk of disease progression versus no intervention. Based on current best evidence, maintenance therapy with lenalidomide is the most efficacious option.